Penggemukan Sapi Potong Berbasis Impor pada PT Sawargi Mulya Sandaya Bandung - Is Zunaini Nursinah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2004)
The objective of this research was economic efficiency determined by domestic resources cost for imported cattle. Descriptive methode was applied in this research, while data shadow price of input production were used in analysis of feedlotters of imported cattle in PT Sawargi Mulya Sadaya. Result of research indicate that Expense of sumberdaya domestic at cxchangc rate of Rp 9.700,- to US1,00 for gift of ransom of mean equal to Rp6.524,83 per US and at gift of maximal ransom equal to Rp8,238.4l, coefficient ofOKC of equal to 0,70 and 0.89. Sensitivity anlysis show that management resources domestic ranch company more efficient than that of farmers.